Fatigue Reliability Prediction of TBM Main Bearings Based on Non-dimensional Interference Model - Chen, Shihui; Zhao, Jian; Liu, Shiming; Ling, Jingxiu; Zhang, Rongchang (Recent Patents on Engineering, 2025)
<span class=
Keywords: non-dimensional interference model